Behavioral and transcriptomic analysis of Trem2-null mice: not all knockout mice are created equal. (11th October 2017) - Kang, Silvia S; Kurti, Aishe; Baker, Kelsey E; Liu, Chia-Chen; Colonna, Marco; Ulrich, Jason D; Holtzman, David M; Bu, Guojun; Fryer, John D
Abstract: It is clear that innate immune system status is altered in numerous neurodegenerative diseases. Human genetic studies have demonstrated that triggering receptor expressed in myeloid cells 2 ( TREM2 ) coding variants have a strong association with Alzheimer's disease (AD) and other neurodegenerative diseases. To more thoroughly understand the impact of TREM2 in vivo, we studied the behavioral and cognitive functions of wild-type (WT) and Trem2 −/− (KO) mice during basal conditions and brain function in the context of innate immune stimulation with peripherally administered lipopolysaccharide (LPS). Early markers of neuroinflammation preceded Aif1 and Trem2 upregulation that occurred at later stages (24–48 h post-LPS). We performed a transcriptomic study of these cohorts and found numerous transcripts and pathways that were altered in Trem2 −/− mice both at baseline and 48 h after LPS challenge. Importantly, our transcriptome analysis revealed that our Trem2 −/− mouse line (Velocigene allele) results in exaggerated Treml1 upregulation. In contrast, aberrantly high Treml1 expression was absent in the Trem2 knockout line generated by the Colonna lab and the Jackson Labs CRISPR/Cas9 Trem2 knockout line. Notably, removal of the floxed neomycin selection cassette ameliorated aberrant Treml1 expression, validating the artifactual nature of Treml1 expression in the original Trem2 −/− Velocigene line. Clearly further studies are needed to decipher whether the Treml1 transcriptional artifact is functionally meaningful, but our data indicate that caution is warranted when interpreting functional studies with this particular line. Additionally, our results indicate that other Velocigene alleles or targeting strategies with strong heterologous promoters need to carefully consider downstream genes.